The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-30969-7
|View full text |Cite
|
Sign up to set email alerts
|

Phase Modulators Based on High Mobility Ambipolar ReSe2 Field-Effect Transistors

Abstract: We fabricated ambipolar field-effect transistors (FETs) from multi-layered triclinic ReSe2, mechanically exfoliated onto a SiO2 layer grown on p-doped Si. In contrast to previous reports on thin layers (~2 to 3 layers), we extract field-effect carrier mobilities in excess of 102 cm2/Vs at room temperature in crystals with nearly ~10 atomic layers. These thicker FETs also show nearly zero threshold gate voltage for conduction and high ON to OFF current ratios when compared to the FETs built from thinner layers.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…1. Its anisotropic optical and electronic properties can be utilized to produce fieldeffect transistors [5][6][7] and photodetectors 8,9 . Moreover, it is reported that thin layer of ReSe 2 may be also used to fabricate ReS 2 /ReSe 2 heterojunction functioning as diodes or solar cells 10 .…”
Section: Introductionmentioning
confidence: 99%
“…1. Its anisotropic optical and electronic properties can be utilized to produce fieldeffect transistors [5][6][7] and photodetectors 8,9 . Moreover, it is reported that thin layer of ReSe 2 may be also used to fabricate ReS 2 /ReSe 2 heterojunction functioning as diodes or solar cells 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Many interesting physical properties of ReSe 2 have been reported, such as layer‐dependent electrical and optoelectronic responses, polarized Raman spectroscopy, and polarization‐sensitive photoresponsivity . Recent studies have reported electron and hole mobilities as high as ≈10 2 cm 2 V −1 s −1 at low temperature and it shows potential as an alternative material to graphene for next‐generation circuits. However, there have been few studies to date on the electrical characteristics of this material, and a lack of investigations focused on its electronic device design.…”
Section: Introductionmentioning
confidence: 99%
“…[28] All other Raman spectra are consistent with previous reports. [29][30][31] In addition, other characterizations using photoluminescence for MoS 2 , MoSe 2 , WS 2 , and WSe 2 , and atomic force microscopy (AFM) for MoTe 2 are shown in Figures S1 and S2, Supporting Information, indicating high quality and uniformity, and offer complimentary validation of film thickness.…”
mentioning
confidence: 99%